2018
DOI: 10.18521/ktd.336102
|View full text |Cite
|
Sign up to set email alerts
|

Yalın Metodolojinin Hastane Laboratuvar Süreçlerinin İyileştirilmesinde Kullanılması (Toyota Üretim Sistemi- Spaghetti Diyagramı)

Abstract: Mühendislik alanında süreç iyileştirmede yaygın olarak kullanılan yalın metotlar, hizmet sektöründe de kullanılmaya başlanılmıştır. Değer ve israf kavramları yalın metodolojide yaygın olarak kullanılmaktadır. Biz bu çalışmada süreç akış şeması çizmeden önce, yalın araçlardan spagetti (makarna) diyagramı çizerek israf kavramına odaklandık ve daha ergonomik iş ortamı geliştirmeyi hedefledik. Metot: Çalışma İzmir Aliağa Devlet Hastanesinde Şubat 2015 ve Eylül 2015 tarihleri arasında yapılmıştır. Ölçümlerde kaizen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The elimination of movement waste by changing the physical area in laboratories has a positive effect on preventing errors, increasing the productivity of employees and decreasing turnaround time (Protzman et al, 2015). As a result of the current research, the change in location made in the Previous studies have shown that unnecessary walking and motion in laboratories can be avoided with the lean management studies (Hayes et al, 2014;Yerian et al, 2012;Yalcin et al, 2018;Quetz et al, 2015). The prevention of unnecessary movement with ergonomic work areas created with lean practices also provides the opportunity for more samples to be examined in the laboratory (Quetz et al, 2015).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The elimination of movement waste by changing the physical area in laboratories has a positive effect on preventing errors, increasing the productivity of employees and decreasing turnaround time (Protzman et al, 2015). As a result of the current research, the change in location made in the Previous studies have shown that unnecessary walking and motion in laboratories can be avoided with the lean management studies (Hayes et al, 2014;Yerian et al, 2012;Yalcin et al, 2018;Quetz et al, 2015). The prevention of unnecessary movement with ergonomic work areas created with lean practices also provides the opportunity for more samples to be examined in the laboratory (Quetz et al, 2015).…”
Section: Discussionmentioning
confidence: 83%
“…As a result of the current research, the change in location made in the pathology laboratory eliminated an average of 230,000 unnecessary steps per year. Previous studies have shown that unnecessary walking and motion in laboratories can be avoided with the lean management studies (Hayes et al , 2014; Yerian et al , 2012; Yalcin et al , 2018; Quetz et al , 2015). The prevention of unnecessary movement with ergonomic work areas created with lean practices also provides the opportunity for more samples to be examined in the laboratory (Quetz et al , 2015).…”
Section: Discussionmentioning
confidence: 99%